Supplementation with omega‐3 or omega‐6 fatty acids attenuates platelet reactivity in postmenopausal women - Adriana Yamaguchi; Livia Stanger; John Cody Freedman; Amanda Prieur; Rachel Thav; Jennyfer Tena; Theodore R. Holman; Michael Holinstat (Clinical and Translational Science, 2022)
Abstract Postmenopausal women are at increased risk for a cardiovascular event due to platelet hyperactivity. There is evidence suggesting that ω‐3 polyunsaturated fatty acids (PUFAs) and ω‐6 PUFAs have cardioprotective effects in these women. However, a mechanistic understanding of how these fatty acids regulate platelet function is unknown. In this study, we supplemented postmenopausal women with fish oil (ω‐3 fatty acids) or evening primrose oil (ω‐6 fatty acids) and investigated the effects on their platelet activity. The effects of fatty acid supplementation on platelet aggregation, dense granule secretion, and activation of integrin αIIbβ3 at basal levels and in response to agonist were tested in postmenopausal women following a supplementation and washout period. Supplementation with fish oil or primrose oil attenuated the thrombin receptor PAR4‐induced platelet aggregation. Supplementation with ω‐3 or ω‐6 fatty acids decreased platelet dense granule secretion and attenuated basal levels of integrin αIIbβ3 activation. Interestingly, after the washout period following supplementation with primrose oil, platelet aggregation was similarly attenuated. Additionally, for either treatment, the observed protective effects post‐supplementation on platelet dense granule secretion and basal levels of integrin activation were sustained after the washout period, suggesting a long‐term shift in platelet reactivity due to fatty acid supplementation. These findings begin to elucidate the underlying mechanistic effects of ω‐3 and ω‐6 fatty acids on platelet reactivity in postmenopausal women. Hence, this study supports the beneficial effects of fish oil or primrose oil supplementation as a therapeutic intervention to reduce the risk of thrombotic events in postmenopausal women. https://clinicaltrials.gov/ct2/show/NCT02629497.